Reconstruction techniques and associated morbidity in minimally invasive gastrectomy for cancer: insights from the GastroBenchmark and GASTRODATA databases - Schneider, Marcel André; Kim, Jeesun; Berlth, Felix; Sugita, Yutaka; Grimminger, Peter P.; Wijnhoven, Bas P. L.; Overtoom, Hidde; Gockel, Ines; Thieme, René; Griffiths, Ewen A.; Butterworth, William; Nienhüser, Henrik; et al. (Annals of surgery, 2024)
Objective/Background: Various anastomotic and reconstruction techniques are used for minimally invasive total (miTG) and distal gastrectomy (miDG). Their effects on postoperative morbidity have not been extensively studied. Methods: MiTG and miDG patients were selected from 9356 oncological gastrectomies performed in 2017-2021 in 43 centers. Endpoints included anastomotic leakage (AL) rate and postoperative morbidity tested by multivariable analysis. Results: Three major anastomotic techniques [circular stapled (CS); linear stapled (LS); and hand sewn (HS)], and 3 major bowel reconstruction types [Roux (RX); Billroth I (BI); Billroth II (BII)] were identified in miTG (n=878) and miDG (n=3334). Postoperative complications, including AL (5.2% vs 1.1%), overall (28.7% vs 16.3%), and major morbidity (15.7% vs 8.2%), as well as 90-day mortality (1.6% vs 0.5%) were higher after miTG compared with miDG. After miTG, the AL rate was higher after CS (4.3%) and HS (7.9%) compared with LS (3.4%). Similarly, major complications (LS: 9.7%, CS: 16.2%, and HS: 12.7%) were lowest after LS. Multivariate analysis confirmed anastomotic technique as a predictive factor for AL, overall, and major complications. In miDG, AL rate (BI: 1.4%, BII 0.8%, and RX 1.2%), overall (BI: 14.5%, BII: 15.0%, and RX: 18.7%), and major morbidity (BI: 7.9%, BII: 9.1%, and RX: 7.2%), and mortality (BI: 0%, BII: 0.1%, and RY: 1.1%%) were not affected by bowel reconstruction. Conclusions: In oncologically suitable situations, miDG should be preferred to miTG, as postoperative morbidity is significantly lower. LS should be a preferred anastomotic technique for miTG in Western Centers. Conversely, bowel reconstruction in DG may be chosen according to the surgeon’s preference.
Gesehen am 27.06.2025